2020
DOI: 10.1038/s41467-020-18489-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of smoking trajectory and meta-analysis of smoking status in 842,000 individuals

Abstract: Here we report a large genome-wide association study (GWAS) for longitudinal smoking phenotypes in 286,118 individuals from the Million Veteran Program (MVP) where we identified 18 loci for smoking trajectory of current versus never in European Americans, one locus in African Americans, and one in Hispanic Americans. Functional annotations prioritized several dozen genes where significant loci co-localized with either expression quantitative trait loci or chromatin interactions. The smoking trajectories were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 82 publications
3
114
1
Order By: Relevance
“…These findings align with both the strong phenotypic relationship between smoking and alcohol use and the known genetic overlap between these traits. 5,10,26 Interestingly, in both the AFR and EUR samples, these associations were no longer significant after covarying for the primary TUD diagnosis, suggesting that the association between PRS and these phenotypes may be mediated by the TUD diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…These findings align with both the strong phenotypic relationship between smoking and alcohol use and the known genetic overlap between these traits. 5,10,26 Interestingly, in both the AFR and EUR samples, these associations were no longer significant after covarying for the primary TUD diagnosis, suggesting that the association between PRS and these phenotypes may be mediated by the TUD diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…While previous genome-wide association studies (GWAS) have identified numerous genetic variants associated with smoking and smoking-related phenotypes [55][56][57][58][59][60] , functional interpretation of these variants remains challenging. Genetic variants could directly alter poly(A) motifs and RBP binding sites to modulate APA events, and several studies have been undertaken in recent years to systematically map novel apaQTLs and their disease etiologies [61][62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…To address this gap in knowledge, we leverage the Million Veteran Program (MVP) cohort, a longitudinal mega biobank with on-going recruitment of Veterans who receive care from the Veterans Health Administration (VA) and has contributed to numerous biomedical and genomics studies [29][30][31]. The VA is the largest single-payer healthcare system in the US and has over 20 years of electronic health record (EHR) data for 6 million annual active users nationwide which will allow to examine the history of clinical risk factors and comorbidities that may be associated with COVID-19.…”
Section: Introductionmentioning
confidence: 99%